Computational scheme for breakup of 11Be on light targets - Valiolda, D; Janseitov, D.M.; Melezhik, V.S. (Eurasian Journal of Physics and Functional Materials, 2026)
We investigate the Coulomb breakup of the 11Be halo nuclei on a light (carbon) target within nonperturbative time-dependent approach including the low-lying resonance 5/2+ of 11Be (E= 1.232 MeV). We had found considerable contribution of the low-lying resonances ( 5/2+ , 3/2− and 3/2+ ) to the breakup cross section of 11Be on a heavy (208Pb) target at our previous calculations. The developed computational scheme is extended to study the breakup of 11Be on a light target. This work is the initial step, where the convergence and accuracy of the computational scheme is tested. Recommended Citation Valiolda, D. S.; Janseitov, D. M.; and Melezhik, V.S. (2023) "Computational scheme for breakup of 11Be on light targets," Eurasian Journal of Physics and Functional Materials: Vol. 7: No. 3, Article 3. DOI: https://doi.org/10.32523/ejpfm.2023070303